The impact of collaboration in the development of Sustainable Supply Chains: The case of the Manufacturing Clusters in Nuevo León, México - Martinez Gonzalez, Alejandra Isabel (2016)
Some stakeholders such as government and buyers are pressuring companies to implement sustainability practices in their operations and in their supply chain. The Cluster strategy is proposed by Porter as a way of collaboration that links companies who are part of the same industry. This research will identify if companies collaborating in clusters are developing Sustainable Supply Chain Practices proposed by Pagell and Wu, and if companies are perceiving those practices useful to improve their operations.